Magic art, folklore, and rural tales in Le Pouldu: André Breton, Paul Gauguin, and Charles Filiger. Issue 2 (3rd April 2018) - Parkinson, Gavin
Abstract: Surrealist art and writing are usually viewed in the context of the modern urban space, but this article coordinates a series of poetic, novelistic, and painted scenes in a rural context to argue for an alternative version of the movement as one concerned with geographical, philosophical, and epistemological medieval stereotypes. These are broached by means of three original theses: that Paul Gauguin's painting had a particular and, till now, unremarked resonance among the later Surrealists; that Brittany took on a privileged status in the movement in the early 1950s; and that an interest in esotericism was not born in the 1940s in Surrealism, as is commonly imagined, but earlier, in the mid-1930s. These proposals are developed initially through close examination of the first but mainly the final part of André Breton's book L'Amour fou ( Mad Love, 1937), especially its evocation of folk tales and pagan legends through its citation of Cinderella (1697), Mary Webb's Gone to Earth (1917), and David Garnett's Lady into Fox (1922). From here, the argument is made that historical and personal events in and close to Le Pouldu that are related in Mad Love, which led Breton to view that southern part of Brittany as enchanted, amplified and inflected Surrealism's interest in Gauguin and the region in the 1950s. I also claim that this understanding on Breton's part is indissociable from his collecting habits of the later period, when he acquired several works by Gauguin's contemporary, the artist Charles Filiger. Ultimately, I use field research in Le Pouldu and close examination of Gauguin's paintings of the region to argue for Breton's intimacy with that location and its artists, which been overlooked until now, understood through the imagined pagan past of the terrain, and experienced in an enchanted present.